INTELLECTUAL CAPITAL AS A DRIVER OF SUSTAINABILITY AMONG SOCIAL ENTREPRENEURS - Ni Putu Sri Harta Mimba; Ni Ketut Rasmini; I.G.A.M. Asri Dwija Putri; Putu Agus Ardiana; Ida Ayu Ary Putri Adnyani (Akurasi : Jurnal Studi Akuntansi dan Keuangan, 2025)
Social entrepreneurs drive inclusive development but face financial, institutional, and risk-related barriers. This study investigates how intellectual capital (IC)—human, structural, and relational—supports the sustainability of social enterprises in Bali, Indonesia. Using survey data from 100 entrepreneurs analysed with PLS-SEM, the results show that perceived barriers are insignificant, while risks negatively affect sustainability. IC has a positive direct impact but no moderating effect, indicating that it acts as an independent driver. The study contributes to the understanding IC’s role in resource-constrained contexts and recommends strengthening capacity-building and ecosystem support to enhance sustainable enterprise performance.